Model Pengentasan Kemiskinan Melalui Kebijakan PKH di Jawa Tengah - Iva Faulana; Indri Murniawaty; Rusdarti Rusdarti (Oikos : Jurnal Ekonomi dan Pendidikan Ekonomi, 2021)
Poverty is a major problem faced by all countries including Indonesia. One of the poverty alleviation programs in Indonesia is the Family of Hope Program (PKH). Central Java Province is one of the provinces that has a relatively high number of poor people among the provinces in Indonesia. The purpose of this study is to examine the success of the PKH Program in poverty alleviation efforts in Central Java. The purpose of this study is to describe the implementation of the Family Hope Program (PKH) in poverty alleviation efforts through PKH policies in Central Java Province, starting from the education, health and social welfare components. The theory used in this study is the vicious circle theory of poverty. The method used in this research is descriptive qualitative, with data collection techniques namely observation, interviews, and study documentation. The results of this study indicate that the Family Hope Program (PKH) in Wonosobo Regency, Central Java Province has succeeded in reducing poverty levels in addition to that the implementation of the Family Hope Program (PKH) in Wonosobo Regency has run quite well. But in reality there are still many Beneficiary Families (KPM) who depend on PKH assistance, given that such assistance is only temporary and is more focused on breaking the poverty chain. Keywords: Poverty; Program Keluarga Harapan